Prototipe Sistem Monitoring Gangguan Motor Tiga Fasa Berbasis IoT - Wicaksono, Emanuel Purwadi; Haryudo, Subuh Isnur (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2023)
-. In the industrial world, three-phase motors are widely used because they have simple construction, easy maintenance, constant rotation, cheap, high reliability and have a high power factor. However, when operating a three-phase motor, disturbances often occur such as voltage imbalance, current imbalance, excessive load, and even overheat. This research was carried out to produce a three-phase motor disturbance monitoring system that can be accessed via the web which is easy to access and has good accuracy values. The research method uses the ADDIE method with a quantitative approach. The average results of motor measurements using the PZEM004T sensor obtained a no-load voltage value of 220V – 223V with an error of 1.04% - 1.95%, a single phase voltage value of 217V – 224.4V with an error of 1.14% - 2, 5%, average current value of 2A – 4.2A with error of 0% - 16.6%, active power value of 144.6W – 790.4W. The results of motor temperature measurements using the LM35 sensor were 38 ºC - 50 ºC with an error value of 1.06% - 2.5%. The RPM measurement results using an optocoupler sensor were 1027 – 2375 with an error value of 0.26% - 58.71%. From the measurement results it is known that the no-load voltage and single phase voltage have good values, there is an imbalance in the current and power used, the motor temperature increases relatively significantly, and it has an unstable RPM.